2020
DOI: 10.1097/sih.0000000000000470
|View full text |Cite
|
Sign up to set email alerts
|

“Who Am I and Why Am I Here?” A Scoping Review Exploring the Templates and Protocols That Direct Actors in Their Roles as Simulated (Standardized) Patients

Abstract: Simulated patients (SPs) are increasingly used in health education and research. The aim of this article was to investigate templates and protocols that enable SPs to accurately and consistently adopt these roles. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for scoping reviews guided the search strategy for articles that detailed such templates or protocols. Embase Classic + Embase, ProQuest ERIC, Ovid MEDLINE, Ovid EMCare, psycINFO, and Scopus were searched, and 17 article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Standardized colleagues portray physicians or other healthcare professionals to be on the receiving end of recommendations and interact in a simulated interprofessional healthcare environment. In an ideal setting, standardized colleagues are played by a healthcare professional because a background that includes clinical training generally produces more realistic encounters 86,87 …”
Section: Standardized Patientsmentioning
confidence: 99%
“…Standardized colleagues portray physicians or other healthcare professionals to be on the receiving end of recommendations and interact in a simulated interprofessional healthcare environment. In an ideal setting, standardized colleagues are played by a healthcare professional because a background that includes clinical training generally produces more realistic encounters 86,87 …”
Section: Standardized Patientsmentioning
confidence: 99%
“…Talwaker et al 4 frame the use of SPs in fulfilling curricular learning objectives through 12 helpful tips. However, neither they nor Davies et al 1 take into account the role of the actor in the construction of the script as being a key factor in the successful implementation of the scenario.…”
mentioning
confidence: 98%
“…In their latest article, Davies et al 1 focus on the implementation of templates and protocols to orient instructors in the construction of scripts to improve the validity and consistency of scenarios with the aim of meeting the objectives established within the learning activity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies used structured scripts for the training of specific psychotherapeutic skills (Coyle et al, 1998), and others used no specific script, but clinical case vignettes (Imel et al, 2014). A recent review (Davies et al, 2021) confirmed that instructions used for SPs varied in terms of structure, length, and depth.…”
mentioning
confidence: 99%